Pengaruh Literasi Akuntansi, Literasi Perpajakan, Dan Sanksi Pajak Terhadap Kepatuhan Pajak Dengan Coretax Sebagai Pemoderasi - Ignasius, Felixs; Tambun, Sihar (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2025)
The purpose of this research is to determine if the Coretax Administration System, a technology-based tax administration system, may mitigate the effects of accounting literacy, tax literacy, and tax penalties on taxpayers' compliance with their tax obligations. This study utilizes a quantitative method in conjunction with causal design. Information was gathered by means of a survey that was sent out to one hundred fifty taxpayers residing in the Jakarta City region who were registered with the KPP. Structural Equation Modeling (SEM) based on Partial Least Squares (SmartPLS) was used to analyze the data. The study found that accounting literacy, tax literacy, and tax penalties all had a favorable and significant effect on tax compliance. There was no statistically significant effect of the Coretax Administration System's moderation variable on enhancing the correlation between the aforementioned three independent variables and tax compliance. In light of the findings, it is clear that digital systems like Coretax do not play a significant moderating role in promoting tax compliance, but that strict sanctions and better education on accounting and taxation principles are critical